Helmintos associados a Norops fuscoauratus (Squamata, Dactyloidae) em brejos de altitude do semiárido brasileiro - Mesquita, Jéssica Maria dos Santos (2020)
Helminthological studies may contribute with valuable information on host biology and conservation. Herein, we provide new data on helminths infecting the lizard Norops fuscoauratus, testing one of the factors considered most important in parasitic ecology: host size. We analysed 25 specimens of N. fuscoauratus from three highland marshes in the Brazilian semi-arid. Eight taxa of helminths belonging to Nematoda, Trematoda and Acanthocephala were found. Physaloptera sp. showed the higher prevalence (40%), with a mean intensity of infection of 3.3 ± 1.46 (1–16) and mean abundance 1.32 ± 0.65 (0–16). Norops fuscoauratus representes four new host records for the helminths Cyrtosomum sp., Pharyngodon travassosi, Strongyloides sp. and Centrorhynchus sp. There is no relationship of host body size (P = 0.79) and mass (P = 0.50) with parasite richness. In addition, the present study contributes to the knowledge of the parasitic fauna of N. fuscoauratus and the Neotropical region.